2009
DOI: 10.1136/bmj.b2269
|View full text |Cite
|
Sign up to set email alerts
|

Chronic wound sepsis due to retained vacuum assisted closure foam

Abstract: Count radiolucent foam pieces used in outpatient vacuum assisted wound closure to prevent chronic sepsis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Retained VAC sponges have rarely been reported in literature. In our brief review, we have identified five earlier cases (3)(4)(5)(6)(7)(8). However, we would like to underline that the lack of reporting in literature does not necessarily reflect Letter to the Editor A. Rencuzogullari the rarity of incidents.…”
Section: Discussionmentioning
confidence: 98%
“…Retained VAC sponges have rarely been reported in literature. In our brief review, we have identified five earlier cases (3)(4)(5)(6)(7)(8). However, we would like to underline that the lack of reporting in literature does not necessarily reflect Letter to the Editor A. Rencuzogullari the rarity of incidents.…”
Section: Discussionmentioning
confidence: 98%
“… Lewis et al [ 69 ] Retrospective Historical cohort of 431 patients after laparotomy for endometrial cancer; 134 patients with wound complications (31 %) Prophylactic NPWT or routine care Direct postoperative application to the surgical site; negative pressure therapy for 4–7 days 23. Beral et al [ 70 ] Case report 67 year old patient with superficial wound dehiscence after TAH + BSO for ovarian cancer VAC Negative pressure therapy for 15 days; dressing replacement every 72 h; portable VAC device for several weeks 24. Sioma-Markowska U.…”
Section: Methodsmentioning
confidence: 99%
“… Lewis et al [ 69 ] Mean overall cost of incision care following NPWT $509 vs. routine care $613 NA Risk of skin blistering following NPWT estimated at 20 % Assumption of 50 % reduction in risk of wound complication following NPWT 23. Beral et al [ 70 ] Wound healing with purulent discharge NA Retained pieces of foam in the wound area NA 24. Sioma-Markowska U.…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have described chronic wound sepsis caused by retention of the foam dressing [23]. Such cases highlight the importance of employing trained clinicians to manage NPWT devices.…”
Section: Complicationsmentioning
confidence: 99%